STRATEGI PEMASARAN DESTINASI MANGROVE WONOREJO DALAM MENDUKUNG KEBERLANJUTAN EKOWISATA KOTA SURABAYA - Sari, Ralita Dewi Kartika; Kurniawati, Ony; Adi, Titok Waskito (Media Mahardhika, 2026)
The Wonorejo Mangrove Tourism Park has significant potential for development as a leading ecotourism destination in Surabaya due to its important ecological functions and high environmental educational value. However, its management and marketing strategies still need to be strengthened to ensure the area's competitiveness, attract more visitors, and maintain environmental sustainability and community involvement. This research aimed to: (1) identify the strengths and weaknesses influencing promotional efforts for the Wonorejo Mangrove Tourism Park in Surabaya; (2) identify the opportunities and threats that could impact the area's development as a sustainable ecotourism destination; and (3) provide recommendations on the most appropriate marketing strategies to increase its appeal while maintaining the sustainability of this environmentally-based tourism area. The research informants consisted of those with direct understanding of the destination management and development process, namely representatives from the Surabaya City Tourism Office, the Wonorejo Mangrove Tourism Park management, and visitors involved in tourism activities. Based on the analysis results, this study recommends a number of marketing strategies, including strengthening tourist attractions, optimal use of digital promotions, improving facilities and infrastructure, increasing human resource capacity, cross-sector collaboration, sustainable environmental management, and strengthening internal regulations.